Tari Moyo : Eksplorasi Budaya Masyarakat Nias dan Spritualitas Kristen - Trinitas Nuryani Dakhi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Moyo Dance or also known as Eagle Dance is a form of traditional art originating from Nias Island in North Sumatra. Historically, this performance was performed at royal events to entertain kings and queens and welcome guests in an honorable manner. The people of Nias live in a cultural environment that is deeply rooted in customs and traditions, although most of this traditional culture is still little known, even among the people themselves. This dance has significant historical and cultural value, reflecting the identity and heritage of the Nias people. With the arrival of Christianity in the 19th century, there was an interesting interaction between local culture and Christian teachings. This article aims to explore how the Moyo Dance is a form of cultural expression that also embodies Christian spirituality, and how these two aspects can complement each other in the lives of the Nias people.